Complicated pulmonary human coronavirus-NL63 infection after a second allogeneic hematopoietic stem cell transplantation for acute B-lymphocytic leukemia: A case report. Issue 25 (25th June 2021) - Li, Zhihui; Meng, Shuo; Zheng, Qinlong; Wu, Tong
Abstract: Rationale: Viruses are the most common pathogens that can cause infection-related non-recurrent death after transplantation, occurring mostly from the early stages of hematopoietic stem cell transplantation (HSCT) to within 1 year after transplantation. Human coronavirus (HCoV)-NL63 is a coronavirus that could cause mortality among patients with underlying disease complications. Serological tests are of limited diagnostic value in immunocompromised hosts and cases of latent infection reactivation. In contrast, macro-genomic high-throughput (DNA and RNA) sequencing allows for rapid and accurate diagnosis of infecting pathogens for targeted treatment. Patient concerns: In this report, we describe a patient who exhibited acute B-lymphocytic leukemia and developed complicated pulmonary HCoV-NL63 infection after a second allogeneic HSCT (allo-HSCT). Six months after the second allo-HSCT, he developed sudden-onset hyperthermia and cough with decreased oxygen saturation. Chest computed tomography (CT) suggested bilateral multiple rounded ground-glass opacities with the pulmonary lobules as units. Diagnoses: HCoV-NL63 was detected by metagenomic next-generation sequencing (NGS), and HCoV-NL63 viral pneumonia was diagnosed. Interventions: The treatment was mainly based on the use of antiviral therapy, hormone administration, and gamma-globulin. Outcomes: After the therapy, the body temperature returned to normal, the chest CT findings had improved on review, and the viral copy number eventually became negative. Lessons: The latest NGS is an effective method for early infection diagnosis. The HCoV-NL63 virus can cause inflammatory factor storm and alter the neutrophil-to-lymphocyte ratio (NLR). This case suggests that the patient's NLR and cytokine levels could be monitored during the clinical treatment to assess the disease and its treatment outcome in a timely manner.